PENGARUH PROFESIONALITAS DAN KUALITAS PELAYANAN TERHADAP CITRA LEMBAGA PADA SUKU DINAS PENANGGULANGAN KEBAKARAN DAN PENYELAMATAN KELURAHAN MANGGARAI JAKARTA SELATAN - Khikmatul Islah; Arrafi Al Hakam (Majalah Ilmiah Dinamika Administrasi (MIDA), 2023)
The performance of Fire Prevention and Rescue Department is deemed slowly by community, this can be seen from the result of the study conducted by Safitri and news on online media. This certainly can affect the institution image of the Fire Prevention and Rescue Department. This study aims at finding out the Influence of Professionalism and Service Quality on Institution Image at Fire Prevention and Rescue Department of South Jakarta at Manggarai Village Area. This study used quantitative approach and is correlational type. The population of this study was 34,871 people at Manggarai Village, South Jakarta using Slovin formula with the sample of 100 people. The sampling technique used was Accidental Sampling. The data sampling technique used was questionnaire and data analysis technique was multiple regression. The result of the study showed that the Influence of Professionalism and Service Quality on Institution Image at Fire Prevention and Rescue Department of South Jakarta at Manggarai Village Area has been proven positive and significant both partially and simultaneously.